사지좌골결합쌍생아의 마취관리 - 김동원; Dong Won Kim; 승익상; Ik Sang Seung; 전민선; Min Seon Jeon (Korean journal of anesthesiology, 1996)
Only 6% of conjoined twins are of the ischiopagus type in which the twins are joined symmetrically at the pelvis and fusion begins at the level of the common umbilicus. Two sets of female ischiopagus tetrapus conjoined twins were born in August, 1994. The longitudinal axis extended in a straight line in opposite directions and the heart, large vessels, musculo-skeletal system and genitourinary tracts were shared. Tetrapus is a subtype in which all 4 extremities are present. At 20 hours of age, separation was successfully performed under general anesthesia, requiring 185 minutes for twin A and 225 minutes for twin B at the Hanyang University Hospital. We describe the associated anomalies, surgical operation and anesthesia management of these 2 sets of ischiopagus tetrapus twins and now, l year after the operation, the two continue to live. (Korean J Anesthesiol 1996; 30: 83~87)